1987
DOI: 10.1083/jcb.105.5.2383
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila laminin: characterization and localization.

Abstract: Abstract. Drosophila laminin was isolated from the medium of Drosophila K~ cell cultures. It was purified by velocity sedimentation, gel filtration, and chromatography. Drosophila laminin is a disulfide-linked molecule consisting of three chains with apparent molecular masses of 400, 215, and 185 kD. In electron micrographs, it has the cross-shaped appearance with globular domains characteristic of vertebrate laminin with closely similar dimensions. The amino acid composition and lectin-binding properties of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 40 publications
4
63
0
Order By: Relevance
“…The following antibodies were used: rabbit anti-Dlg (1:500) (Woods and Bryant, 1991); mouse anti-Orb (1:20) (Lantz et al, 1994); rabbit anti Baz (1:500) (Wodarz et al, 2000); mouse anti-Crb (CQ4,1:20) (Tepass et al, 1990); rabbit anti DG (1:3000; this study); mouse or rabbit anti-βGal (1:5000, Sigma); mouse anti-Neurotactin (BP102; 1:20) (Hortsch et al, 1990); rabbit anti-Laminin (1:3000) (Fessler et al, 1987); ant-Dlt (1:1000) (Bhat et al, 1999); anti-β-HSpectrin (1:1000) (Thomas and Kiehart, 1994); Alexa 488, 568 or 633 goat anti-mouse (Molecular Probes); Alexa 568 or 633 Goat antiRabbit or Rat (Molecular Probes); and Alexa 568 or 633 Phalloidin (Molecular Probes). DAB staining was done with the Vectastain Kit (Vector Laboratories, CA).…”
Section: Histocytochemistrymentioning
confidence: 99%
“…The following antibodies were used: rabbit anti-Dlg (1:500) (Woods and Bryant, 1991); mouse anti-Orb (1:20) (Lantz et al, 1994); rabbit anti Baz (1:500) (Wodarz et al, 2000); mouse anti-Crb (CQ4,1:20) (Tepass et al, 1990); rabbit anti DG (1:3000; this study); mouse or rabbit anti-βGal (1:5000, Sigma); mouse anti-Neurotactin (BP102; 1:20) (Hortsch et al, 1990); rabbit anti-Laminin (1:3000) (Fessler et al, 1987); ant-Dlt (1:1000) (Bhat et al, 1999); anti-β-HSpectrin (1:1000) (Thomas and Kiehart, 1994); Alexa 488, 568 or 633 goat anti-mouse (Molecular Probes); Alexa 568 or 633 Goat antiRabbit or Rat (Molecular Probes); and Alexa 568 or 633 Phalloidin (Molecular Probes). DAB staining was done with the Vectastain Kit (Vector Laboratories, CA).…”
Section: Histocytochemistrymentioning
confidence: 99%
“…Primary antibodies used were: rabbit anti-laminin A antiserum at 1:100 dilution (Fessler et al, 1987), mouse anti-Fasciclin III (7G10-Hybridoma Bank) at 1:1000, mouse anti-GFP at 1:500 (Cell Signalling), rabbit antiactive Caspase 3 at 1:100 (Cell Signalling), mouse anti-EcRB1 at 1:10 (AD4.4 Hybridoma Bank) and mouse anti-EcRA at 1:10 (15G1A-Hybridoma Bank). Secondary antibodies were anti-mouse or anti-rabbit FITC, Cy3 or Cy5 conjugated (Molecular Probes) at 1:250 dilutions.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Whole-mount immunostaining was carried out using standard procedures with antibodies obtained from the Developmental Studies Hybridoma Bank, developed under the auspices of the NICHD and maintained by The University of Iowa, Department of Biological Sciences, Iowa City, IA 52242 against the following targets: DN-cadherin (DN-Ex number 8), Neurotactin (BP106), Futsch (22C10), CNS axons (BP102), Crumbs (Cq4) and Repo (8D12). The following antibodies were also used: monoclonal antibody against Drosophila collagen IV and polyclonal antibodies against Drosophila SPARC (Martinek et al, 2002), Drosophila laminin (α3,5/β1/γ1) (Fessler et al, 1987), Drosophila perlecan (Friedrich et al, 1999) and hunchback (Kosman et al, 1998). Secondary antibodies conjugated to Alexa Fluor 488, Cy3, Cy5 (Molecular Probes) or HRP (Jackson Laboratories) were used.…”
Section: Cuticle Preparation In Situ Hybridization and Antibody Staimentioning
confidence: 99%
“…Laminin is expressed by a broad range of tissues during embryogenesis and, similar to SPARC and collagen Journal of Cell Science 121 (10) , 1992). The laminin antibodies used in this study only recognized fully assembled, extracellular laminin (Fessler et al, 1987) and, thus, haemocyte immunostaining of laminin was not observed. Immunostaining of ES12 wild-type embryos revealed a laminin network that overlies the neuroepithelium (Fig.…”
mentioning
confidence: 99%